Еnergy efficiency in construction - Zhigulina, A.Yu.; Shinguzhieva, A.B.; Kurmaniyazova, N.Zh.; Umereshova, S.G.; Abzalqyzy, A. А. (ЗКАТУ им. Жангир хана, 2024)
The article covers issues of energy efficiency in construction, i.e. design, construction and operation of energy-saving buildings and structures. An energy-efficient building is a set of architectural, planning and engineering solutions that best meet the goals of minimal energy consumption to ensure the microclimate in the premises of the building. A literary review of foreign literature on energy efficiency as a dominant feature of modern types of construction and prospects for the use of energy-saving buildings in construction were carried out. The results show that insufficient thermal resistance of the surrounding structures most significantly reduces the energy efficiency of buildings. The authors examine energy-efficient technologies and composite materials obtained by scientists from the West Kazakhstan Agrarian and Technical university named after Zhangir khan. Methods for increasing energy saving are shown, these include the introduction of fundamentally new types of building structures and the use of new energy-efficient materials. This applies to the construction of both existing and newly introduced buildings and structures. Energy-efficient materials are expanded clay and ceramic bricks, which are obtained from local loams with the addition of oil sludge. They also include foam glass, which is obtained from glass production waste with the addition of various corrective additives. Examples of energy efficient houses from different countries are shown.
Еnergy efficiency in construction / A.Yu. Zhigulina, A. B. Shinguzhieva, N. Zh. Kurmaniyazova, S. G. Umereshova, A. Abzalqyzy, A. A. Ibraimov . - Текст : непосредственный // Ғылым және білім=Наука и образование=Science and education. - 2024. - 1-2 (74). Ч. ІІ. - Р. 243-250. - ISSN 2305-9397
Keywords: бқату; energy saving; composite materials; energy efficiency; energy consumption; technology; West Kazakhstan